The Crisis of Language and The Subject in Spanish Poetry of The 21st Century, in Context: Spirals of Violence and Extravagant Deviations - García Faet, Berta (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
In this article we examine two types of crises, that of language and that of subjectivity, in contemporary Spanish poetry, focusing on authors such as Mariano Peyrou, Abraham Gragera, Rafael Espejo, Carlos Pardo, Luis Bagué Quílez, Daniel Salgado, Carlos Bueno Vera and David Leo García. We rely on the theories of Nietzsche, Hofmannsthal and Lyotard and we trace a genealogy of both crisis; a genealogy that is Western (Paul Celan, John Ashbery...), Latin American (Javier Sologuren, Alejandra Pizarnik...) and Iberian (José Ángel Valente, Álvaro García...). We emphasize the similarities and differences that the writings of these poets born in the seventies and eighties show and suggest that these connections have everything to do with their special denunciation of the violent nature of rationalist thinking. We end up contrasting these authors with some women poets who have also explored the crisis of the word and the I but not from negativity and self-paralysis but from a type of thinking that might be called purposeful and fantastic, such as Erika Martínez, Olalla Castro and Elena Medel.